2015
DOI: 10.1075/lab.5.2.04woo
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of dative alternation by German-English bilingual and English monolingual children

Abstract: Abstract:The vulnerability of the syntax-semantics interface in simultaneous bilingual first language acquisition is still up for debate; while some scholars have found crosslinguistic transfer at this interface, others found no such influence. To determine which kinds of syntax-semantics interface phenomena may be vulnerable, this study examines the acquisition and use of dative alternation by German-English bilingual children and adults compared with English monolingual children and German and English monoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The findings showed that Mazurkerwich's (1984) hypothesis was confirmed i.e., the unmarked constructions were acquired first. In another study, Woods (2012) examined the acquisition of the dative alternation by German-English bilingual and English monolingual children, showing the differences between the two groups. The acquisition of the locative alternation has also been studied by several researchers.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings showed that Mazurkerwich's (1984) hypothesis was confirmed i.e., the unmarked constructions were acquired first. In another study, Woods (2012) examined the acquisition of the dative alternation by German-English bilingual and English monolingual children, showing the differences between the two groups. The acquisition of the locative alternation has also been studied by several researchers.…”
Section: Overviewmentioning
confidence: 99%
“…This instrument was used by other researchers (e.g., Mazurkerwich, 1984;Woods, 2012) to investigate other types of alternation, such as the dative alternation. The two researchers deemed the GJT reliable to test the participants' knowledge of different types of alternation as it elicits fruitful results and deep insight into the participants' answers.…”
Section: The Testmentioning
confidence: 99%
“…A prior analysis of CHILDES data showed that these verbs were used frequently in the DO form and occasionally in the PO form in the child and child-directed speech of five German-speaking children aged 1;6-7;5 (MacWhinney 2000;Leo: Behrens 2006;Cosima, Pauline, Sebastian: Lieven and Stoll 2013;Caroline: Von Stutterheim 2014). Further, most of the verbs are documented in the literature on the acquisition of the dative alternation in German (Eisenbeiss et al 2006;Woods 2015).…”
Section: Sentence Stimulimentioning
confidence: 99%
“…The dative alternation has been a poster child of generative approaches to second language acquisition and widely recognized as an instance of a poverty-of-stimulus phenomenon, since the L2 learner must somehow determine which verbs allow alternating syntactic forms and which ones do not from a limited set of data in the input (Juffs, 1996; Perpiñán and Montrul, 2006; White, 2003). There are several studies of the L2 acquisition of the dative alternation in English by L1 speakers of Spanish (Agirre, 2015), Brazilian Portuguese (Zara et al, 2013), French (Hawkins, 1987; Le Compagnon, 1984; Mazurkewich, 1984), Japanese (Bley-Vroman and Yoshinaga, 1992), Chinese (Chang, 2004), Japanese and Chinese (Inagaki, 1997), Korean and Mandarin (Oh, 2006, 2010; Oh and Zubizarreta, 2006), Korean and Japanese (Whong-Barr and Schwartz, 2002), Russian (De Cuypere et al, 2009–10), Turkish (Marefat, 2005), and German (Jäschke and Plag, 2016; Woods, 2015). These studies, most of them experimental, have addressed the role of L1 transfer on the acquisition of the dative alternation English, the developmental stages L2 learners go through in acquiring the dative alternation, and how L2 learners acquire different subclasses of verbs based on finer-grained semantic and morphological constraints (e.g.…”
Section: How Datives Come and Gomentioning
confidence: 99%